Theories and practices of disability from the Global South: a critical anthropological perspective - Brocco, Giorgio (Frontiers in Health Services, 2024)
“Critical disability studies” (CDS) is an interdisciplinary field of research that examines social, political, economic, racial, gendered and historical constructions of bodily non-normativity across different geopolitical areas and scales. Despite its diverse and multiple contributions and objectives, current research in critical disability studies has been described as mainly focusing on disability issues in the Global North and as having universalizing tendencies. In this context, intersubjective perspectives and empirical data offered by ethnographic works in medical and disability anthropology and related disciplines have been either in accord or tension with the broader field of CDS. On the one hand, this review article illustrates the many ways anthropologists have adopted various research perspectives to explore bodily non-normativity outside settings in the Global North. On the other, it shows the importance of research by anthropologists working on topics related to disability, as well as their recent fruitful collaborations with CDS scholars and approaches. By exploring these epistemological and empirical entanglements, this paper concludes that deeper engagements between CDS and anthropology, as well as a more thorough focus on the ethnographic analysis of bodily non-normativity, can open new creative routes for the analysis of disability in various world contexts.